The brittle and plastic response of quartz. - Glover, Graham John (Centre for Materials Engineering, 2015)
Quartz is the principal mineral constituent of the earth's upper crust and a knowledge of the deformation characteristics of quartz are of geological and technological importance. In common with many ceramic materials, quartz may not satisfy the Von Mises independent slip system criterion and clarification is required on the exact response to an imposed stress system at a given temperature.